Developing the Event, Duration, Latency, and Interval (EDLI) Assessment Techniques to Measure Student Engagement and Motivation in Islamic Religious Education Online Courses - Agus; Mawardi Djamaluddin; Tamrin Taher; Minggusta Juliadarma; Nurhidayat; Nur Rahmah Asnawi; Noviyanti Soleman (Jurnal Pendidikan Agama Islam, 2024)
Purpose – The purpose of this study is to develop Event, Duration, Latency and Interval (EDLI) Assessment Techniques to Measure Student Learning Engagement and Motivation in Online Learning Design/methods/approach – This study used a research and development (R&D) framework by Borg & Gall which consists of (1) Research and information collecting, (2) Planning, (3) Developing preliminary form of product, (4) Preliminary field testing, and (5) Operational field testing. The research subjects were lecturers at 5 universities in North Maluku province who implement online learning, totaling 10 lecturers. Data analysis using the Aiken Index to determine product validity criteria. Findings – The results of the social behavior in online learning experts assessed 83% of the products developed as valid, then experts in the field of learning media assessed 83% of the products developed as valid, finally experts in the field of IT development assessed 83% of the products developed as valid.  Research implications/limitations – The Event, Duration, Latency, and Interval (EDLI) assessment technique guide is applicable for all lecturers conducting online learning. However, due to researcher limitations, product trials during the Operational Field Testing stage cannot be conducted at all universities in North Maluku Province and are restricted to universities in the city of Ternate. Originality/value – The importance of a guide that explains procedures for assessing student performance during online learning is especially related to student motivation and involvement, and the Event, Duration, Latency, and Interval (EDLI) procedure is very relevant for use in assessing student performance during online learning.